2018
DOI: 10.1021/acsami.8b07346
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Atomic Layer Deposition of Metal Oxide Layers for Perovskite Solar Cells with High Efficiency and Stability under Harsh Environmental Conditions

Abstract: Rapid progress achieved on perovskite solar cells raises the expectation for their further development toward practical applications. Moisture sensitivity of perovskite materials is one of the major obstacles which limits the long-term durability of the perovskite solar cells, especially in outdoor operation where rainfall and water accumulation on the solar panels often occur. Micro/nanopinholes within the functional layers of the devices usually lead to water vapor penetration, thus subsequent decomposition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(90 citation statements)
references
References 58 publications
(96 reference statements)
4
83
0
Order By: Relevance
“…Though device encapsulation and interface engineering have been proven to be effective to improve the stability of the perovskite devices externally, [ 17,18 ] improving the inherently unstable nature of perovskite materials should still be considered as the main approach to be investigated. [ 19–22 ] Previous researches have demonstrated that the low formation energy of detrimental defects especially at the surface and grain boundaries is responsible for perovskite deterioration.…”
Section: Figurementioning
confidence: 99%
“…Though device encapsulation and interface engineering have been proven to be effective to improve the stability of the perovskite devices externally, [ 17,18 ] improving the inherently unstable nature of perovskite materials should still be considered as the main approach to be investigated. [ 19–22 ] Previous researches have demonstrated that the low formation energy of detrimental defects especially at the surface and grain boundaries is responsible for perovskite deterioration.…”
Section: Figurementioning
confidence: 99%
“…Bella et al demonstrated the effectiveness of photocurable fluoropolymers as encapsulation on both the transparent as well as the opaque side of the device . Alternative, Lv et al reported that a trilayer of Al 2 O 3 /O−Al−(CH 3 ) 3− x /Al 2 O 3 deposited by atomic layer deposition (ALD) on top of the metal contact of a perovskite solar cell, provides good stability against moisture . Next to the compact ALD Al 2 O 3 layers, the intermediate reactant in between the two Al 2 O 3 films acts as a scavenger of the few water molecules permeating the external layer.…”
Section: Tandem Solar Cellsmentioning
confidence: 99%
“…[14] Other metal oxides have been used as ETL in PSCs, including ZnO and Nb 2 O 5. To avoid high-temperature calcination, Lv et al used low-temperature ALD technology to introduce the pinhole-free TiO 2 layer into PSCs., showing that the degradation of the perovskite layer during the process of fabricating the TiO 2 layer is indeed negligible.…”
Section: Etlmentioning
confidence: 99%
“…Therefore, the TiO 2 layer fabricated by low-temperature ALD can significantly reduce the interfacial charge recombination and enhance the water resistance; with this improvement, the device can finally achieve a PCE of 18.3 %. [14] Other metal oxides have been used as ETL in PSCs, including ZnO and Nb 2 O 5. Similar to TiO 2 , the morphology and structure of ZnO used in PSCs mainly consist of dense planes 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 and nanostructures.…”
Section: Etlmentioning
confidence: 99%
See 1 more Smart Citation